2009
DOI: 10.1016/j.nimb.2009.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Study on the behavior of oxygen atoms in swift heavy ion irradiated CeO2 by means of synchrotron radiation X-ray photoelectron spectroscopy

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…The roughly 2 eV edge shift, which also does not vary significantly between the two ions, indicates partial reduction, as a complete reduction of all Ce 4 þ to Ce 3 þ corresponds to a 7 eV shift 30 . Previous studies 17,18 of CeO 2 irradiated with 200 MeV Xe ions have demonstrated similar oxidation state changes using X-ray photoelectron spectroscopy.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…The roughly 2 eV edge shift, which also does not vary significantly between the two ions, indicates partial reduction, as a complete reduction of all Ce 4 þ to Ce 3 þ corresponds to a 7 eV shift 30 . Previous studies 17,18 of CeO 2 irradiated with 200 MeV Xe ions have demonstrated similar oxidation state changes using X-ray photoelectron spectroscopy.…”
Section: Resultsmentioning
confidence: 59%
“…Although radiation-induced redox effects have been observed in previous studies 14,[17][18][19]44 , this comparative investigation of both valence state changes and structural damage caused by irradiation, in a range of materials, represents the first demonstration of systematic coupling between the two modifications. Reducible materials, with multivalent cations, show structural radiation responses that are fundamentally different from that of non-redox active ThO 2 .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations